New chondrichthyan fin spines from the Pedra de Fogo Formation, Brazil. (July 2017) - Figueroa, Rodrigo T.; Gallo, Valéria
Abstract: The Pedra de Fogo Formation is located at the northeast region of Brazil and possesses a diverse palaeobiota mainly composed by plants and vertebrate remains of Lower Permian age (Cisuralian). The palaeoichthyofauna includes several chondrichthyans ( e.g. Sphenacanthus maranhensis, Taquaralodus albuquerquei, Itapyrodus punctatus and Anisopleurodontis pricei ) but also include osteichthyans as the 'palaeoniscoid' Brazilichthys macrognathus and several actinopterygian and sarcopterygian remains. This variety of fish taxa of both marine and freshwater affinities is important for understanding taxonomical diversity and distribution of vertebrates from Western Gondwana. Here, specimens collected at the Pastos Bons locality, near Nova Iorque at State of Maranhão, are described as two new species for known genera, Sphenacanthus ignis sp. nov. and Bythiacanthus lopesi sp. nov., also a new genus and a new species Rubencanthus diplotuberculatus gen. et sp. nov. that exhibit a distinct pattern of ornamentation from all previously known Palaeozoic chondrichthyans. These new records highlight the importance of more palaeontological studies for the Pedra de Fogo Formation and enlarge the variety of chondrichthyan for the locality. Highlights: Pedra de Fogo Formation sited at NE Brazil possesses a diverse palaeobiota. Ornamentation of chondrichthyan fin spines is not remarkable bellow generic level. New genus exhibits a distinct pattern of ornamentation from all Palaeozoic sharks. These new data claim more research on the palaeoichthyofauna of this formation.